Invisible Emmie - Libenson, Terri (Libenson, Terri. Emmie & friends, 2017)
This is the story of two totally different girls -- quiet, shy, artistic Emmie and popular, outgoing, athletic Katie -- and how their lives unexpectedly intersect one day, when an embarrassing note falls into the wrong hands. All the crushes, humiliation, boredom, and drama of middle school are compressed into one surprising day.